Ban On Plastic Bags Usage: Is It A Right Move? An Empirical Study On Consumer Perception And Practice - Gooi, Bee Sung (2010)

(untitled)
Penggunaan beg plastik telah menyebabkan manfaat dan kerugian dalam kehidupan kita sehari-hari.